A New Methodology for Optimal Design of Hybrid Vibration Control Systems (MR + TMD) for Buildings under Seismic Excitation - Brandão, Francisco Da Silva; Miguel, Letícia Fleck Fadel (Shock and Vibration, 2023)
This study proposes a new methodology, based on the optimization procedure by a metaheuristic algorithm, for designing a hybrid vibration control system to mitigate the dynamic response of buildings under nonstationary artificial earthquakes (NSAEs). For illustration purposes, a 10-story shear building is studied. The hybrid control system involves the use of an MR damper (MR) and a tuned mass damper (TMD) located in different places of the structure. To describe the behavior of the MR, the modified Bouc–Wen model (MBW) was used. To calculate the damping force of the MR, the clipped optimal control associated with linear quadratic regulator (LQR), CO-LQR, was considered. The optimization was performed using the whale optimization algorithm (WOA) and seismic load generated by the Kanai–Tajimi spectrum. Different control scenarios were evaluated: MR-OFF, MR-ON, CO-LQR, STMD, and CO-LQR (MR + TMD) to determine the best control scenario that can effectively control the structure. Overall, the optimized hybrid control scenario (MR + TMD) was the only one able to adapt all story drifts to the control criterion of the consulted normative. Then, CO-LQR (MR + TMD), designed via the methodology proposed in this work, proved to be the best alternative to control the seismic response of this building.